1979
DOI: 10.1107/s002188987901219x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of strain distribution in elastically bent materials by X-ray intensity measurement

Abstract: A method for quantitative determination of local curvature in elastically bent perfect crystals is described. The method is based on X-ray intensity measurements, and a comparison of experimentally determined values with those derived from diffraction theory gives satisfactory agreement. The method was applied to determine the strain gradient and strain concentration in the vicinity of the notch of an elastically bent crystal. The experimental results were compared with those derived from a similar model based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

1980
1980
2004
2004

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 12 publications
(16 reference statements)
1
20
0
2
Order By: Relevance
“…Для сла-бого и промежуточного уровней деформации приближение геомет-рической оптики [1], являющееся главным членом разложения в ряд точного решения [2], показывает [3,4], что зависимость ИОС R i (B) описывается последовательно параболическим и линейным законами соответственно для малой и промежуточной деформации. При больших же градиентах деформации экспериментальные зави-симости могут быть количественно описаны соответствующими формулами точного решения, предусматривающими приближение ИОС с ростом B к ее кинематическому пределу [2].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Для сла-бого и промежуточного уровней деформации приближение геомет-рической оптики [1], являющееся главным членом разложения в ряд точного решения [2], показывает [3,4], что зависимость ИОС R i (B) описывается последовательно параболическим и линейным законами соответственно для малой и промежуточной деформации. При больших же градиентах деформации экспериментальные зави-симости могут быть количественно описаны соответствующими формулами точного решения, предусматривающими приближение ИОС с ростом B к ее кинематическому пределу [2].…”
Section: Introductionunclassified
“…Для Интегральная дифрактометрия наноразмерных дефектов в монокристалле 55 идеальных изогнутых кристаллов известно [1][2][3], что с ростом де-формации изменяются дифракционные условия с глубиной в непо-глощающем кристалле для каждой из двух волновых мод (происхо-дит искривление этих мод). В частности, в [3,4] показано, что это обстоятельство приводит к возникновению линейной зависимости R i (1/) для промежуточных значений деформации. Учет же интер-ференционного поглощения, которое увеличивается с ростом де-формации, и, следовательно, уменьшает ПИОС и конкурирующего влияния, т. е. увеличения ПИОС за счет уширения кривых отраже-ния при изменении дифракционных условий, сопровождающегося миграцией точек возбуждения по дисперсионной поверхности, обеспечивает наблюдающуюся немонотонность хода рассматривае-мых кривых при отрицательных деформациях.…”
Section: Introductionunclassified
“…The integrated intensities were recorded by counter methods from small areas, limited by a pinhole of 100/~m diameter (Kalman & Weissmann, 1979). This study has shown that the measured intensities are proportional to the local effective curvatures; the variation of local curvature in front of the notch is in turn proportional to the strain concentration.…”
Section: Strain Measurements Of Notched Silicon By X-ray Topographymentioning
confidence: 99%
“…It has been shown (Kalman & Weissmann, 1979) that by measuring the X-ray intensities la of an elastically bent silicon crystal as a function of the distance d from the notch root, the respective local, effective curvatures Qa can be determined. Far removed from the notch root, this curvature Qi, being unaffected by the notch, is equal to the curvature impressed by the bending device.…”
Section: Determination Of the Strain Concentration Factor K~ In The Vmentioning
confidence: 99%
See 1 more Smart Citation